2006
DOI: 10.2147/ciia.2006.1.3.253
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aging on respiratory system physiology and immunology

Abstract: With the looming expansion of the elderly population of the US, a thorough understanding of “normal” aging-related changes on the respiratory system is paramount. The respiratory system undergoes various anatomical, physiological and immunological changes with age. The structural changes include chest wall and thoracic spine deformities which impairs the total respiratory system compliance leading to increase work of breathing. The lung parenchyma loses its supporting structure causing dilation of air spaces: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

21
500
5
39

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 794 publications
(565 citation statements)
references
References 29 publications
21
500
5
39
Order By: Relevance
“…More specifically, in our study we observed that with increasing age, there is an increase in the COP value, a fact that can probably be explained by changes that occur in the respiratory system 28,30 . Evidence has shown a reduction in alveolar surface, increase in the alveolar dead space, conditions that are associated with pulmonary hyperinflation and a reduction in the alveolar-capillary diffusion capacity 30,31 , in addition to a lower VE 29 , which, together with the stiffening of blood vessels 32 contributes to a worst ratio or increase in the V/Q 28,[30][31][32] .…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…More specifically, in our study we observed that with increasing age, there is an increase in the COP value, a fact that can probably be explained by changes that occur in the respiratory system 28,30 . Evidence has shown a reduction in alveolar surface, increase in the alveolar dead space, conditions that are associated with pulmonary hyperinflation and a reduction in the alveolar-capillary diffusion capacity 30,31 , in addition to a lower VE 29 , which, together with the stiffening of blood vessels 32 contributes to a worst ratio or increase in the V/Q 28,[30][31][32] .…”
Section: Discussionsupporting
confidence: 57%
“…Regarding the ventilatory variables, it is known that, over the years, there is also a reduction in respiratory muscle strength 26 and some ventilatory indicators, such as forced expiratory volume in one second (FEV1) 27 and forced vital capacity (FVC ) 28 , as well as a less effective response to the increase in PaCO2 at rest 29 .…”
Section: Discussionmentioning
confidence: 99%
“…(12) In our study, we found a higher prevalence of dyspnea in patients over 60 years of age, a finding that has been reported in another study (13) and might be due to age-related changes in pulmonary function. (14) Fibrotic/atelectatic changes on chest X-rays were also more common among the patients over 60 years of age, which suggests that many of them had a history of TB. However, we do not have consistent data regarding the history of TB in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…Aging of the lungs is associated with decreased pulmonary elastic recoil, chest wall compliance, and respiratory muscle strength, as well as an increase in alveolar dead space 3, 4. The basis for these functional changes includes loss of elastin content and resultant increase airspace dimensions.…”
mentioning
confidence: 99%
“…Functional consequences of the morphologic alterations in the lungs of older people include increased residual volume and functional residual capacity, decreased maximal expiratory flow rate and forced vital capacity, lower diffusion capacity, and higher ventilation/perfusion mismatch 5. Although no clinical signs are seen in healthy subjects as a result of these functional changes, there is a decrease in the reserve capacity of the lung in the presence of disease and these changes may impact exercise capacity 3. In conjunction with this decline in lung function, over 45% of elderly humans demonstrate an increase in airway responsiveness to nonspecific agonists such as histamine 6.…”
mentioning
confidence: 99%